Estudo longitudinal de marcadores sorológicos para o imunodiagnóstico da toxoplasmose aguda humana. - Geisa Baptista Barros (2009)
Toxoplasma gondii is thought to infect one third of the world population. Acute infection is often asymptomatic, but if acquired during pregnancy, T. gondii can be transmitted vertically, through the placenta, from mother to fetus, who is at high risk of developing severe disease. The commercially available serological tests have several limitations such as lack of quality control and conflicting results on specificity, and/or sensitivity, making the diagnosis of T. gondii acute infection difficult to perform. In addition , noneof the diagnostics studies published thus far , have evaluated sequential longitudinal sera panels from the same patients over a 12-month period. To our knowledge there is also no study on the use of flow cytometry (FC) in the measurement of the functional affinity (IgG avidity) and analysis IgG subclasses in acute toxoplasma infection. The present study, a longitudinal descriptive analytical prospective cohort study, was designed to evaluate surrogate markers for the diagnosis of acute and recent pasttoxoplama infection. From June, 2005 to July, 2007, 31 patients with acute toxoplasma infection were enrolled in the study and followed for 12 months after the beguining of symptoms. Pared sera samples from all 31 patients were collected at the following month time points: 1, 2 & 3 (group 1: acute infection), 4, 6 & 8 (group 2: convalescent recent infection) and 10 & 12 (group 3: convalescent late infection). Sera were analyzed by IgG and IgM indirect Immunofluorescence assay (IFA), IgG, IgM and IgA Enzime-linked immunosorbent Assay (ELISA), IgG, IgM and IgG avidity Enzyme-linked fluorescent assay (ELFA). A CF assay was standardized to quantify IgG and IgM antibodies, IgG subclasses and IgG avidity. Two cut-points were chosen for the ELISA, IFA and ELFA assays and also for FC: a) according to manufactures inserts and b) cut-off points adjusted according to sensitivity and specificity results using Receiver OperatingCharacteristic (ROC) curve analysis. Two different discriminant analyses were used inother to classify the pacients in one of the three time point groups. The present study reassure the limitations of using IgA to identify stage- specific diagnosis of infection. IgM assays displayed the most diagnostic sensitivities for detection of acute infection: 100% for ELISA, ELFA and FC and 89,5% for IFA. On the 12th month time point sera collection, persistent positive IgM antibodies were detected on ELISA in 26 of 31 patients (83,8%), on ELFA in 83,3% (25/30), on FC in 32,6%(16/31) and on IFA in 29% (9/31) patients. The results of ELFA IgG avidity showed progressive and consistent avidity during the 12-month follow-up period. The FC IgG avidity results were more specific. Positive correlation between assays was only detected with IgM in ELISA, ELFA and FC. Thiscorrelation was high with ELISA and ELFA in all time points, with ELISA and FC on months 3 to 8 and with ELFA and FC from the second on. There was no significant correlation for IgG and IgM antibodies between IFA and the other assays. Analysis of variance between all time points were statistically significant for all antibodies assays but IgG4. There was a statistically significant difference between the first and the months thereafter when IgG assays with ELISA and FC were compared. IgG IFA assay results did not distinguish infection between the 12 month time points. However, the ELISA, ELFA and FC IgM assay distinguished the first and second month sera from the others. Among IgG subclasses, only IgG3 distinguished infection time points. The ROC curve analysis was important in establishing cut-off points, which can be used ina future protocol in an attempt to discriminate between acute and more recent past infection. In our study, the best approach model for the temporal toxoplasma infection diagnosis was FC avidity, IgM ELFA and ELFA avidity. This model separated all patients from Group 1 from patients in Group 3 and vice-versa. This is the first report on the use of FC for IgG avidity, IgG subclasses and IgM in the diagnosis of acute toxoplasmosis. This assay showed high specificity for IgG avidity, IgG3 and IgM anti-toxoplasma antibodies and can be used to separate recent acquired from late convalescent infections.